Pharmacists' nonprescription syringe dispensing perceptions and behaviors: A three-state descriptive analysis. (1st April 2021) - Hagemeier, Nicholas E.; Dowling-McClay, KariLynn; Baladezaei, Mahnaz; Curtis, Sabrina J.; Spence, Matthew
Highlights: Community pharmacies serve as syringe access points for people who inject drugs. Most syringe dispensing research has been conducted in major metropolitan areas. The Appalachian study counties are at increased risk of HIV and HCV dissemination. Nonprescription syringe dispensing varied across state lines. State policy is necessary but insufficient to impact pharmacist syringe dispensing. Abstract: Background: One approach to increasing the reach of syringe programs in rural areas could be through provision of syringes at community pharmacies. This study evaluated relationships between state-specific syringe policies, pharmacy, and pharmacist characteristics and pharmacists' nonprescription syringe dispensing behaviors in a 3- state Appalachian region at high risk for HIV and HCV transmission. Methods: We conducted a telephone census of community pharmacies in the Appalachian counties of North Carolina, Tennessee, and Virginia from April–June 2018. Behaviors studied included having ever sold syringes without a prescription, quantity of individuals to whom nonprescription syringes were dispensed in the past 30 days, having ever denied a request for nonprescription syringes, and past 30-day denial of nonprescription syringe requests. Behavioral intention and perceptions of legality were elicited. Results: A response rate of 52.3 % was achieved (N = 391). North Carolina pharmacists reported increased past 30-day dispensing, less denial of nonprescription syringe requests, and decreased justification for syringe dispensing (proof of medical need) as compared to Tennessee and Virginia pharmacists. Behavioral intention to dispense did not vary by state but did vary by political affiliation. Perceptions of syringe dispensing legality in NC were significantly different from those in TN and VA. Conclusions: Significant differences in pharmacists' perceptions and behaviors were noted across state lines with North Carolina pharmacists reporting more engagement in syringe dispensing as compared to pharmacists in Tennessee and Virginia. Policy allowing pharmacists to dispense syringes to people who inject drugs appears to foster some but not all pharmacist engagement in this harm reduction intervention.